Beyond Strict Illiteracy: Abstracted Learning Among Low-Literate Users - Thies, Indrani Medhi; Menon, Raghu; Cutrell, Ed; Toyama, Kentaro (4th IEEE/ACM Conference on Information and Communication Technologies and International Development (ICTD) 2010, London, UK, IEEE, 2010)
One of the greatest challenges in designing applications for developing communities is that potential users may have limited literacy. Past work in UI design for low-literate users has focused on illiteracy as the inability to read per se, with little recognition to other cognitive differences between literate and non-literate users. In this paper, we investigate the correlation between literacy and cognitive skills for conceptual abstraction using video-based skills training. We performed a controlled experiment that compared 28 non-literate and 28 literate participants from low-income communities in India. Results confirm that both the groups did worse when a skill required generalization from instructional material, compared with the case when instructional material was specifically and exactly tailored to the skill. Literate participants did better than non-literate participants all-around on this learning task. In addition, we found that diversification of examples within instructions helped literate participants in transfer of learning, but did not help non-literate participants. We conclude that ICT UI and content for low-literate users should be sensitive to issues beyond strict illiteracy, to additional cognitive differences among these users.